Untimely Applause Was a Distraction; Comment on “Shanghai Rising: Health Improvements as Measured by Avoidable Mortality since 2000” - Yan Fei; Jian Zhang (International Journal of Health Policy and Management, 2015)
The paper published in the January 2015 issue of this journal by Gusmano and colleagues entitled “Shanghai rising: health improvements as measured by avoidable mortality since 2000” has spurred this commentary. We discuss controversial issues surrounding the concept of avoidable mortality in health service research in general and Gusmano’s study in particular. The impact of overall social development on mortality may be underappreciated in Gusmano’s report; the innovative efforts of healthcare professionals to use cutting-edge technology and evidenceapproved preventive strategies to reduce healthcare cost and improve the life quality of community members may not necessarily come to fruition in death reduction, and might be undervalued, too. More critically, the shape and magnitude of emerging health issues in Shanghai, such as accidents and injuries, pollution-related cancers, may be camouflaged in Gusmano’s report. We conclude this commentary by suggesting the most urgent questions to be addressed in the future studies.